Sagot :
Step-by-step explanation:
[tex]1. \: 3x + 6 = 5x[/tex]
[tex]5x - 3x = 6[/tex]
[tex]2x = 6[/tex]
[tex] \frac{2x}{2} = \frac{6}{2} [/tex]
[tex]x = 3[/tex]
[tex]2. \: 3x + 5 = 26[/tex]
[tex]3x = 26 - 5[/tex]
[tex]3x = 21[/tex]
[tex] \frac{3x}{3} = \frac{21}{3} [/tex]
[tex]x = 7[/tex]
[tex]3. \: 2x - 2 = 143[/tex]
[tex]2x = 143 + 1[/tex]
[tex]2 x = 144[/tex]
[tex] \frac{2x}{2} = \frac{144}{2} [/tex]
[tex]x = 72[/tex]
[tex]4. \: 5x - 1 = 4x + 3[/tex]
[tex]5x - 4x = 3 + 1[/tex]
[tex]2x = 4[/tex]
[tex] \frac{2x}{2} = \frac{4}{2} [/tex]
[tex]x = 2[/tex]
[tex]5. \: 3x + 54 = 5x[/tex]
[tex]5x - 3x = 54[/tex]
[tex]2x = 54[/tex]
[tex] \frac{2x}{2} = \frac{54}{2} [/tex]
[tex]x = 27[/tex]
[tex]6. \: 7x - 44 = 3x[/tex]
[tex]7x - 3x = 44[/tex]
[tex]4x = 44[/tex]
[tex] \frac{4x}{4} = \frac{44}{4} [/tex]
[tex]x = 11[/tex]